Endotracheal Intubation without Neuromuscular Blocking Agent in Patient with Fracture Cervical Spine C1 and C4 Underwent Fusion C12 and C46 - Suarjaya, I Putu Pramana; Purwanto, Osmond; Aldy, Aldy; J. Sutawan, Ida Bagus Krisna (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
About 30% of cervical spine fractures involve injuries to the C1 and C2 vertebrae, which are considered unstable. Ensuring the stability of the injured cervical spine throughout perioperative period, including preoperative examinations, anesthesia induction, laryngoscopy, and intubation, is crucial for anesthesiologists. A 40-year-old woman suffered neck pain following a motorcycle accident, suffering a Spinal Cord Injury ASIA Impairment Scale (SCI AIS) E, a fracture of the C5 vertebral body (CV) classified as AO Spine Type A2, a Jefferson Type IV fracture, and mild head trauma. She underwent surgical fusion of the C1C2 and C4C6 vertebrae under general anesthesia, which included dexmedetomidine, propofol, sevoflurane, and fentanyl without any neuromuscular blocking agents (NMBA). The primary goal of perioperative airway management in cervical injury is a secured airway, while maintaining cervical stability without inflicting secondary injury. The cervical muscle group is essential for maintaining cervical stability, and the use of NMBA may jeopardize this stability, necessitating external cervical stabilization, especially during laryngoscopy and intubation. Induction agents in combination with opioid, widely used to facilitate laryngoscopy and intubation without using NMBA. Anesthesiologists must precisely arrange the management of cervical spine injuries patient to avoid secondary injury and improve surgical outcomes.